Study on the performance of emulsified asphalt recycled subgrade based on the evaluation of semi-rigid milling material. (21st March 2022) - Yu, Liting; Xie, Jie; Li, Rui; Hu, Jiulong; Pei, Jianzhong
Highlight: A large amount of semi-rigid base was milled and not fully utilized, resulting in wasting, dumping and pollution problems. In this regard, this paper provided a new method. Based on the analysis of the research performance of the milling material, the original semi-rigid subgrade was regenerated by emulsified asphalt into a subgrade with flexibility to enhance the structural performance of the regenerated pavement. The results concluded that emulsified asphalt cold regeneration of semi-rigid subgrade road use had practical feasibility. The results showed that the cracking toughness of the recycled subgrade increased with the amount of cement used, but was able to resist the risk of cracking caused by loading to a certain extent. Therefore, a certain amount of cement can be added to the recycled subgrade, but the maximum amount of cement needed to be limited in order to ensure the cracking resistance of the recycled subgrade. The research results can be used for pavement subgrade regeneration, which improves the efficiency of pavement construction and provides a solution for environmentally pavement construction. Abstract: Semi-rigid basement materials had high strength and good integrity therefore it extensively used on pavements of all grades. However, it had serious and widespread early damages, so the treatment of waste semi-rigid subgrade was about to become an important subject in reconstruction. A large amount of semi-rigid base was milled and not fully utilized, resulting in wasting, dumping and pollution problems. In this regard, this paper provided a new method. Based on the analysis of the research performance of the milling material, the original semi-rigid subgrade was regenerated by emulsified asphalt into a subgrade with flexibility to enhance the structural performance of the regenerated pavement. The performance of the recycled subgrade was evaluated in terms of its degree of flexibility, mechanical properties and crack resistance, compared to the original semi-rigid subgrade. The results concluded that emulsified asphalt cold regeneration of semi-rigid subgrade road use had practical feasibility. The research results can be used for pavement subgrade regeneration, which improves the efficiency of pavement construction and provides a solution for environmentally pavement construction.